Multi-agent reinforcement learning based dynamic optimization algorithm of CRE offset for heterogeneous networks - Cheng ZHANG; Jiaye ZHU; Zening LIU; Yongming HUANG (Tongxin xuebao)
To cope with the high throughput demand caused by the proliferation of wireless network users, a multi-agent reinforcement learning based dynamic optimization algorithm of cell range expansion (CRE) offset was proposed for interference scenarios in macro-pico heterogeneous networks.Based on the value decomposition network framework of collaborative multi-agent reinforcement learning, a personalized online local decision of CRE offset for all pico-base stations was achieved by reasonably utilizing and interacting the intra-system user distribution and their interference levels among pico-base stations.Simulation results show that the proposed algorithm has significant advantages in increasing system throughput, balancing the throughput of each base station and improving edge-user throughput, compared to CRE=5 dB and distributed Q-learning algorithms.